Offering flowers, feeding skulls : popular goddess worship in West Bengal - McDaniel, June (Oxford University Press, 2004)
In 'Offering Flowers, Feeding Skulls', June McDaniel provides an overview of Bengali goddess worship or Shakti. She identifies three major forms of goddess worship, and examines each through its myths, folklore, songs, rituals, sacred texts, and practitioners, tracing these strands through Bengali culture.